Changes in the Systemic Expression of Sirtuin-1 and Oxidative Stress after Intravitreal Anti-Vascular Endothelial Growth Factor in Patients with Retinal Vein Occlusion - De-Kuang Hwang; Yuh-Lih Chang; Tai-Chi Lin; Chi-Hsien Peng; Ke-Hung Chien; Ching-Yao Tsai; Shih-Jen Chen; Kuan-Hsuan Chen; Min-Yen Hsu (Biomolecules, 2020)
Objectives: Retinal vein occlusions (RVO) are associated with systemic risk factors. However, the ocular occlusive events might also influence a patient’s systemic condition. This study tried to investigate serum biomarkers associated with oxidative stress, before and after intravitreal anti-vascular endothelial growth factor (aVEGF) therapy in patients with RVOs. Methods: Newly-onset RVO patients were categorized into two groups: comorbid with macular edema requiring aVEGF therapy (treatment group) and no edema (observation group). Age and sex-matched patients (who received cataract surgery) were included as the control group. Intravitreal ranibizumab with a pro-re-nata regimen were administered. Serum samples were collected prior to treatment, at 6 and 12 months after therapy/observation and were collected once before controls who received cataract surgery. mRNA expression of sirtuin-1, its downstream genes, anti-oxidative biomarkers, and proinflammatory cytokines were measured. Results: There were 32, 26, and 34 patients enrolled in the treatment, observation, and control groups, respectively. The expressions of sirtuin-1 and its downstream genes were significantly lower in patients with RVO compared with the control group. Sirtuin-1 gene expression increased after 1 year of aVEGF therapy in the treatment group but remained unchanged in the observation group. Biomarkers of oxidative stress and proinflammatory cytokines were reduced after 1 year of aVEGF therapy. These biomarkers remained with no changes in the observation group. Conclusions: Our study showed that the systemic oxidative stress increased in RVO patients. The aVEGF therapy could alter the gene expression of anti-oxidative proteins and reduce systemic oxidative stress in these patients.